THE EFFECT OF VIUSID© PET TO ACTIVITY AND CAPASITY OF MACROPHAGES IN MICE - Nuradi, Yoga Pratama; Suartha, I Nyoman; Ardana, Ida Bagus Komang (Buletin Veteriner Udayana; Vol. 9 No. 2 Agustus 2017, 2017)
Glycyrrhizic acid, which is the active ingredient of Viusid© Pet, is commonly used to enhance the immune response. This study was conducted to determine the effect of Viusid© Pet on macrophage activity and capacity. Thirty-six BALB/c mice were divided into 3 groups. The first group as control was given aquades, the second group was given a dose of Viusid© Pet 0.1 ml, and the third group was given a dose of Viusid© Pet 0.2 ml. All groups were given treatment from the first day until the seventh day. On the eighth day, each mouse was injected intraperitoneally by Staphylococcus aureus bacteria. The activity and capacity of macrophage cells were calculated from the peritoneal fluid smear by calculating the percentage of phagocytes performing phagocytosis in 100 macrophage cells. The phagocytic capacity was determined by the amount of Staphylococcus aureus bacteria that is phagocytosed by 50 active phagocyte cells. The activity of phagocytosis increases with increasing doses of Viusid © Pet. It was concluded that the highest macrophage activity and capacity was achieved in the treatment group with the dosage of Viusid © Pet 0.2 ml (825.33 ± 291,73). While the activity and the lowest phagocytic capacity of the negative control group (578.08 ± 186.94) was followed by the dose group of 0.1 ml (654.83 ± 266.09).